2022
DOI: 10.1039/d2ma00815g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of hole carrier density in p-type α-SnWO4 by exploiting oxygen defects

Abstract: The development of p-type oxide semiconductors has shown promise in overcoming limitations restricting the practical usage of oxide semiconductors and the realization of innovative functional devices. Through numerous studies based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Minohara et al fabricated a p-type α-SnWO 4 by controlling the annealing temperature or the concentration of oxygen defects. 44,45 α-SnWO 4 samples with n-type conductivity, however, are more common. Several density functional theory (DFT) calculations have been performed to understand the electronic structure of α-SnWO 4 .…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Minohara et al fabricated a p-type α-SnWO 4 by controlling the annealing temperature or the concentration of oxygen defects. 44,45 α-SnWO 4 samples with n-type conductivity, however, are more common. Several density functional theory (DFT) calculations have been performed to understand the electronic structure of α-SnWO 4 .…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Semiconductors containing post-transition metal cations with a lone pair ( n s 2 n p 0 ) electronic configuration (Sn 2+ , Sb 3+ , Pb 2+ , Bi 3+ ) are a special class of photoabsorbers in solar-to-energy conversion systems. The filled s orbitals interact with anion orbitals to form the upper valence band, providing unique optoelectronic properties such as defect tolerance, reduced hole effective mass, , and shallow ionization potentials. These effects have led to promising photo­(electro)­catalysts such as BiVO 4 , , Bi 4 NbO 8 Cl, , and Pb 2 Ti 2 O 5.4 F 1.2 …”
mentioning
confidence: 99%
“…The generation of electrons by the formation of interstitial oxygen was also reported in α-SnWO 4 . 18 However, the source of electrons is still an open question because the interstitial oxygen is not an electrically active defect on the basis of theory. 51,52 Finding v suggested that the O 2p z and Sn 5s,5p hybridization states forming the lone pair were destabilized in the thin SnO films.…”
mentioning
confidence: 99%
“…Via application of these functionalities, high-efficiency perovskite solar cells, lead-free ferroelectrics, and p-type oxide semiconductors and photocatalysts for water splitting have been designed and developed. The development of p-type oxide semiconductors with a wide bandgap is essential for realizing innovative electronic devices for ultralow power consumption in transparent , and high-power , electronics. Recently, state-of-the-art p-type oxide semiconductors have been developed on the basis of the lone-pair states of Sn 2+ or Bi 3+ . The optical bandgap was manipulated by transforming the chemical composition from infrared to ultraviolet. , Furthermore, hole densities of Sn 2+ - or Bi 3+ -based complex oxides were controlled over several orders of magnitude using precise defect control or intentional chemical doping. , …”
mentioning
confidence: 99%
See 1 more Smart Citation